An Empirical Study on the Impact of Centralized Drug Procurement Policy on the Growth Capacity of Pharmaceutical Companies - Li, Xiaomeng (Journal of Global Economy, Business and Finance, 2025)
In 2018, China issued the “4+7 Cities Drug Centralized Procurement Document”, which reduced drug prices and benefited the people, but also had a certain impact on the growth ability of pharmaceutical companies. Based on the data of A- share listed companies in the pharmaceutical industry, this paper uses the multi-period double difference method to conclude that the drug centralized procurement policy has an overall promoting effect on the growth ability of pharmaceutical companies, and promotes corporate growth by increasing the company’s sales gross profit margin, but it also has a certain inhibitory effect. The implementation of the policy will increase the company’s sales expenses, thereby affecting the company’s growth.